An Introduction to Systematic Theology - Athappilly, Sebastian (Journal of Dharma, 1993)
W Pannenberg, An Introduction to Systematic Theology, Michigan: William B. Eerdmans Publishing Company, Grand Rapids Michigan: Wm. B. Eerdmans Publishing Co., 1991, pp. v+69.